A one-pot and two-stage Baeyer–Villiger reaction using 2, 2′-diperoxyphenic acid under biomolecule-compatible conditions. Issue 5 (22nd February 2022) - Gan, Shaoyan; Yin, Jingru; Yu, Zhiyou; Song, Lijuan; Shi, Lei
Abstract : A Baeyer–Villiger reaction using 2, 2′-diperoxyphenic acid was developed and this reaction could be biomolecule-compatible. Abstract : An efficient oxidant named 2, 2′-diperoxyphenic acid was newly developed, and it exhibited high stability as revealed by thermogravimetric analysis (TGA) coupled with differential scanning calorimetry (DSC). On applying this reagent in the Baeyer–Villiger oxidation, the reaction featured a markedly broad substrate scope and good functional group tolerance, giving rise to the corresponding products in good to excellent yields. Particularly, in the case of pure water or 1× Phosphate Buffered Saline (1× PBS) serving as the solvent, the protocol could work well, resulting in yields ranging from 81% to 98%. Moreover, the catalytic asymmetric version of the BV reaction was explored as well, affording the corresponding products in good yields and medium ee. Remarkably, the corresponding biological compatibility and greenness assessment indicated that this reagent had favorable application prospects in the biomedical and green manufacturing fields. Meanwhile, mechanistic studies including 18 O isotope effect experiments and DFT computations suggested that this reaction followed the generally accepted mechanism of BV oxidation.